Resolva o sistema através do método da adição :
2x + 3y = 5
3x - 2y = 12
Soluções para a tarefa
Respondido por
1
Multiplica- se a 1° por 3 e a 2° por (-2 )
Fica assim:
6x+9y=15
-6x+4y=-24
Somando:
13y=-9 ==> y=-9/13
Substituindo:
Na 1°:
x=-11/13
Fica assim:
6x+9y=15
-6x+4y=-24
Somando:
13y=-9 ==> y=-9/13
Substituindo:
Na 1°:
x=-11/13
Perguntas interessantes
Português,
11 meses atrás
Matemática,
11 meses atrás
Ed. Física,
11 meses atrás
Português,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás